Canadiens, Acadiens, and Canada: Knowledge and Ethnicity in Labour History - Ferland, Jacques (Labour/Le Travailleur, 2002)
Abstract By distinguishing between Canadien and Acadien workers, on the one hand, and Canada workers, on the other, this essay examines some of the cognitive implications of L/LT’s epistemological commitment to a Canada-centered interpretation of labour history, particularly with respect to francophone working-class minorities. It argues that this labour history journal is representative of how emphasis on Canada-based workers and labour yields its own definition of class experience, a geopolitical definition that does not necessarily correspond to the ethnically-grounded “national” aspirations and struggles of French-Canadian and Acadian workers.